Verbal and Non-Verbal Means of Expressing Neutrality in the Communicative Behavior of a Mediator - A. S. Kinderknekht (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the communicative behavior of a mediator, whose professional activity is subject to certain norms, rules and principles. The principle of neutrality in the communicative behavior of the mediator is considered in detail. The efforts of two specialists: a lawyer, a practicing mediator, and a linguist who completed a basic course of mediation is combined in the article. The confidentiality of information related to the mediation procedure determined the choice of the main research methods: linguistic self-observation in combination with reflection of professional experience and included observation of the choice of language, speech and non-verbal means in quasi-real training situations. The study identified verbal and non-verbal means that allow the mediator to remain impartial and independent in mediation. Verbal means of neutrality are analyzed at the macro and micro levels of the language system and the speech activity of the mediator. It was revealed that the principle of neutrality is manifested in the mediator's open message about his role as a neutral intermediary, as well as in special technological methods of mediation: echo technique, resume and idea development. On the subject of neutrality, sound reactions, kinetic, visual and spatial signals of the mediator are analyzed. The restrictions and prohibitions in the communicative behavior of the mediator are determined. The conclusion is drawn about the caution of using the considered tools in specific conflict / dispute situations.